THE POTENTIAL USED OF EPIPELIC DIATOM AS BIOINDICATOR OF WATER QUALITY: part I - Tri Retnaningsih Soeprobowati; Hendarko Soegondo; Boedi Hendarto; Indro Sumantri; Budiyanto Toha (JOURNAL OF COASTAL DEVELOPMENT, 1999)
Biomonitoring methods for water quality, such as coli form content, diversity and evenness indices of macrobenthic invertebrates and plankton which are recently used, actually have some weaknesses. Escherichia coli only indicated pollution caused by faecal coli; macrobenthic invertebrates have not ability to live in all substratum, whereas the population of phytoplankton are affected by current as they are floating in the surface water. Therefore, the method which are more effective have to be developed. Epipelic diatoms have potential characteristics as bioindicator of water quality because the have ability to accumulate physic-chemical component of aquatic ecosystem and respond it immediately. This research is conducted in order to find out a new alternative of biomonitoring method ( species indices of diatoms ) which are more significant, effective and efficient by determine water quality map absed on diatoms and determines the species which responsible to the grouping. Sediments samples were taken from 7 rivers in the Northern Coast of Central Java (called Pantura): Karanggeneng-Rembang, Juana-Pati, Banjir Kanal Timur-Semarang, Banjir Kanal Barat-Semarang, Banger-Pekalongan, Pekalonghan-Pekalongan, and Gung-Tegal. Temperature, dissolved oxygen, salinity, pH and turbidity were measure in-situ. Analysis of water and sediment samples include total nitrogen, total phosphorus,silica, heavy metals of Cu, Cr, and Cd. Extraction, preparation and identification of diatoms followed Wetzel & Likens (1991) and Round (1993). The`data were then analysed using Primer package progamme version 4.0 which is produced by Plymouth Marine Laboratory, United Kingdom (Carr, 1997). The Multi Dimentional Scaling (MDS) ordination was done to make grouping and was followed by SIMPER analysis to determine responsible species (Clarke & Warwick, 1994). Based on diatom community, 7 river Pantura could be divided into 3 groups: Group I, consisted of Gung and Pekalongan Rivers, Group II of Banjir Kanal Timur, Barat and Banger Rivers and Group III Karenggeneng and Juana Rivers. Synedra ulna was responsibled for those grouping and are therefore could be promoted as bioindicator of water quality in the Indonesian river. Research still should be developed, especially for diatoms in the bottom layer of sediment samples to reconstruct ecological condition in the past and to predict the condition in the future.